A Case Report of complete appendiceal duplication on the normal site of a single caecum: A new variant? - Ngulube, Allan; Ntoto, Crispin O.M; Matsika, Derek; Ndebele, Wedu; Dube, Ngqabutho Sanders; Gapu, Paradzai (Elsevier Ltd, 2021)
Introduction: Duplicated appendix is an uncommon entity, typically discovered as an incidental finding during surgery for appendicitis or other abdominal pathologies. It may be associated with other congenital malformations. We report a case of a male neonate incidentally discovered to have an unrecognized variant of duplicated appendix during a laparotomy plus diversion colostomy for imperforate anus at 4 days of age.